Solution-synthesized chiral piezoelectric selenium nanowires for wearable self-powered human-integrated monitoring. (February 2019) - Wu, Min; Wang, Yixiu; Gao, Shengjie; Wang, Ruoxing; Ma, Chenxiang; Tang, Zhiyuan; Bao, Ning; Wu, Wenxuan; Fan, Fengru; Wu, Wenzhuo
Abstract: Smart sensing devices with high stretchability and self-powered characteristics are essential in future generation wearable human-integrated applications. Here we report for the first time scalable synthesis and integration of selenium (Se) nanowires into wearable piezoelectric devices, and explore the feasibility of such devices for self-powered sensing applications, e.g., physiological monitoring. The ultrathin device can be conformably worn onto the human body, effectively converting the imperceptible time-variant mechanical vibration from the human body into distinguishable electrical signals, e.g., gesture, vocal movement, and radial artery pulse, through straining the piezoelectric Se nanowires. Our results suggest the potential of solution-synthesized Se nanowire a new class of piezoelectric nanomaterial for self-powered biomedical devices and opens doors to new technologies in energy, electronics, and sensor applications. Graphic abstract: A wearable self-powered human-integrated sensor is developed using solution-synthesized piezoelectric selenium (Se) nanowires. Highlights: Wearable piezoelectric nanogenerator is fabricated using solution-grown selenium nanowires as the active layer. The nanogenerator has reliable durability. The device is cable of being applied as self-powered sensors for human-integrated sensing and monitoring.